Comparison of irisin hormone expression between thyroid cancer tissues and oncocytic variant cells - Ugur, Kader; Aydin, Suleyman; Kuloglu, Tuncay; Artas, Gokhan; Kocdor, Mehmet Ali; Sahin, Ibrahim; Ozercan, Ibrahim Hanefi (Dove Medical Press Ltd, 2019)
Objective: The incidence of thyroid cancer has been continuously increasing. The main objective of this study was to investigate irisin expression in various thyroid pathologies and to compare these expression patterns with irisin expression in healthy thyroid tissues. Methods: The study groups consisted of 20 cases each of control thyroid tissue, Hashimoto's thyroiditis, thyroid papillary carcinoma, oncocytic papillary carcinoma, follicular thyroid carcinoma, oncocytic follicular thyroid carcinoma, medullary thyroid carcinoma, anaplastic thyroid carcinoma. Irisin expression was evaluated using immunohistochemistry. Irisin levels in thyroid tissue supernatants were measured using ELISA. Results: Patients with HT showed increased irisin expression compared with controls (p<0.05). In addition, mild immunoreactivity was observed in the thyroid tissues of patients with papillary carcinoma while significantly increased irisin immunoreactivity was observed tissues of patients with oncocytic papillary carcinoma (p<0.05). There was no difference in irisin immunoreactivity in thyroid tissues between patients with follicular carcinoma and controls. However, irisin immunoreactivity was higher in tissues of patients with oncocytic follicular carcinoma than in tissues of patients with follicular carcinoma (p<0.05). No irisin immunoreactivity was observed in tissues of patients with medullary carcinoma, a malignant tumor the thyroid; however, irisin expression was significantly increased in tissues of patients with anaplastic carcinoma compared with that in tissues of controls (p<0.05). Furthermore, in all thyroid tissues with irisin expression, irisin immunoreactivity was observed in follicular cells, indicating that irisin is produced by these cells. Conclusion: Irisin is a novel potential immunohistochemical marker for differentiating oncocytic variants of papillary and FTCs from papillary and follicular thyroid cancers.
Keywords: thyroid cancer; irisin; immunohistochemistry; diagnostic biomarker